Mechanisms and Trends of Guaiacol Hydrodeoxygenation on Transition Metal Catalysts - Morteo-Flores, Fabian; Roldan, Alberto (Frontiers in Catalysis, 2022)
Understanding the mechanisms of guaiacol’s catalytic hydrodeoxygenation (HDO) is essential to remove the oxygen excess in bio-oils. The present work systematically examines guaiacol’s HDO mechanisms to form benzene on six transition metal (TM) catalysts using density functional theory calculations. The results suggested a preferable Caryl−O bond scission on Ni (111) and Co (0001), whereas on Fe (110), the Caryl–OH bond scission is the most likely pathway. The C−O scission on Pd (111) and Pt (111) is not energetically feasible due to their high activation barriers and endothermic behaviour. Fe (110) also demonstrated its high oxophilic character by challenging the desorption of oxygenated products. A detailed analysis concludes that Co (0001) and Ni (111) are the most favourable in breaking phenolic compounds’ C−O type bonds. Brønsted-Evans-Polanyi (BEP) and transition state scaling (TSS) models were implemented on the catalytic results to derive trends and accelerate the catalyst design and innovation. TSS demonstrated a reliable trend in defining dissociation and association reaction energies. The phenyl ring-oxo-group and the metal-molecule distances complement the catalysts’ oxophilicity as selectivity descriptors in the HDO process.